Synthesis of recycled PET membranes for water vapor transport application - ADDA BENATTIA, Djellal; BENALI, Sara Chourouk (My University, 2019)
A new potential solution for PET plastic bottles recycling has been developed. This new step provides a breakthrough solution to broken down PET plastic waste. It is based on collecting plastic waste and reprocessing it into new membranes which are useful for gas separation. Recycled PET polymer is recovered from water waste bottles. Asymmetric flat sheet membranes M1, M2, M3, M4 and M5 are prepared by the addition of PEG with same difference of the added quantity into recycled PET. Wet/dry gas precipitation phase technique is used for membranes preparation, the obtained thickness was in the range of 60-100 µm. The fabricated membranes were investigated to evaluate the performance of PET membranes and the effect of hydrophilic PEG polymer addition on water vapor permeability and heat resistance. The morphology and water vapor permeability of prepared membranes were improved by the addition of PEG polymer.
Keywords: PET; PEG; Membrane; Gas separation; Asymmetric flat sheet; Wet/dry gas precipitation; Perméabilité